Penerapan Media Pembelajaran Augmented Reality untuk Meningkatkan Pemahaman Konsep Pendidikan Islam Bagi Peserta Didik - Masrizal (Program Studi Manajemen Pendidikan Islam, 2023)
The background of this research focuses on the application of Augmented Reality (AR) technology to enhance the understanding of abstract concepts in Islamic Education for students. Although AR has been applied in various educational fields, its use in the context of Islamic Education remains limited. The purpose of this research is to explore how AR can help students understand Islamic concepts more interactively and contextually. The methodology used in this study is a qualitative approach with observation, interviews, and literature analysis related to the application of AR in education. The principal results of the study indicate that AR can simplify students' understanding of abstract Islamic concepts, such as the concept of God, Prophets, and the afterlife. The use of AR also creates a more engaging and enjoyable learning experience, providing clearer visualizations of the material being taught. The major conclusion of this research is that the application of AR has great potential to improve students' understanding of Islamic Education concepts and contributes significantly to the innovation of more effective and engaging religious learning methods.